Properties of the strains Enterococcus haemoperoxidus and E. moraviensis, new species among enterococci - Lauková, A; Svec, P; Strompfová, V; Stĕtina, V; Sedlácek, I (Folia microbiologica, 2007)
Antibiotic susceptibility or resistance, urease activity, detection of the structural genes for bacteriocin production, bacteriocin activity as well as sensitivity of the isolates to enterocins (Ent) A and M were determined in 23 isolates of new species Enterococcus haemoperoxidus and E. moraviensis. The majority of the strains were antibiotic sensitive and exhibited low urease activity (< 10 nkat/mL). The most frequently detected genes for Ent were entA and entP. However, only the strain 466 of E. haemoperoxidus produced an antibacterial substance with inhibitory activity against 21 G+ indicators. It was partially purified reaching an activity of up to 12 800 AU/mL. This bacteriocin active strain also possessed the genes for EntA and EntP. The other strains did not inhibit the indicator strains. The substance produced by the 466 strain was active even after a 5-months storage at +4 and -20 degrees C. This substance has proteolytic and hydrophilic character, pH optimum of bacteriocin production by this strain being between 4 and 7. While E. moraviensis strains showed sensitivity to EntA (produced by E. faecium EK13) and to EntM (produced by E. faecium AL41), E. haemoperoxidus strains were sensitive to EntA (except strain 382) but less sensitive to the treatment by EntM.
Keywords: Urease; mikrobiologie vody; bakteriociny; Enterococcus; Drug Resistance, Bacterial; bakteriální léková rezistence; sladká voda; mikrobiální testy citlivosti; Microbial Sensitivity Tests; ureasa; Fresh Water; Water Microbiology; Bacteriocins